Presencia del síndrome de úlcera gástrica en equinos de la policía militar (2012)
ABSTRACT: The equine gastric ulcer syndrome (EGUS) has a multifactorial nature with a high and variable prevalence in populations of horses subjected to sport activities and high physical demand. The aim of this study was to describe the frequency of presentation of gastric ulcers in horses of the military police that carried out activities of training, patrolling and inactivity. 32 Brazilian race riding horses aged between 3 and 20 years were evaluated clinically and gastroscopy, gastric lesions were located and classified by number and severity score. A 43.8% of equines showed ulcers, with 37.5% and 6.3% affecting nonglandular and glandular mucus, respectively. No association was reported between the type of activity performed by the animals and the degrees of ulceration found. These results show the presence of EGUS in this type of animals without showing clinical signs and decrease in performance.